(untitled) (International Journal of Research in Pharmaceutical Sciences and Technology, 2026)
Schiff bases are an important class of compounds in medicinal chemistry because of their diverse biological activities and ability to coordinate with metal ions. Thiazole-based Schiff bases, especially those derived from 2-amino-5-methylthiazole, are of interest for developing new antimicrobial agents. Objective: The present study aimed to synthesize, characterize, and evaluate the antibacterial activity of a series of heterocyclic azo Schiff base ligands derived from 2-amino-5-methylthiazole. Methods: Five azo Schiff base ligands (BC1–BC5) were prepared through diazotization of aminothiazole derivatives followed by coupling with activated aromatic compounds. The synthesized compounds were purified by recrystallization and characterized using melting point analysis and FTIR spectroscopy. Antibacterial activity was assessed by the agar well diffusion method against Bacillus licheniformis and Pseudomonas aeruginosa at concentrations of 50 and 100 μg/mL. Ciprofloxacin was used as the standard drug. Results: All compounds were obtained in good yields and showed characteristic FTIR peaks confirming the formation of the azo and azomethine groups. The synthesized ligands exhibited measurable antibacterial activity against both test organisms. Among the compounds, BC3 and BC1 showed comparatively higher activity, though their zones of inhibition were lower than those of ciprofloxacin. The results indicate that substituent variation influenced antibacterial potency. Conclusion: The synthesized thiazole-based azo Schiff base ligands demonstrated promising antibacterial activity and may serve as lead compounds for further structural modification and biological evaluation. Their results support the potential of heterocyclic azo Schiff base frameworks in the development of new antimicrobial agents.